Microscopy visualisation confirms multi‐species biofilms are ubiquitous in diabetic foot ulcers - Johani, Khalid (Int Wound J, 2017)
Increasing evidence within the literature has identified the presence of biofilms in chronic wounds and proposed that they contribute to delayed wound healing. This research aimed to investigate the presence of biofilm in diabetic foot ulcers (DFUs) using microscopy and molecular approaches and define if these are predominantly mono‐ or multi‐species. Secondary objectives were to correlate wound observations against microscopy results in ascertaining if clinical cues are useful in detecting wound biofilm. DFU tissue specimens were obtained from 65 subjects. Scanning electron microscopy (SEM) and peptide nucleic acid fluorescent in situ hybridisation (PNA‐FISH) techniques with confocal laser scanning microscopy (CLSM) were used to visualise biofilm structures. Next‐generation DNA sequencing was performed to explore the microbial diversity. Clinical cues that included the presence of slough, excessive exudate, a gel material on the wound bed that reforms quickly following debridement, poor granulation and pyocyanin were correlated to microscopy results. Of the 65 DFU specimens evaluated by microscopy, all were characterised as containing biofilm (100%, P < 0·001). The presence of both mono‐species and multi‐species biofilms within the same tissue sections were detected, even when DNA sequencing analysis of DFU specimens revealed diverse polymicrobial communities. No clinical correlations were identified to aid clinicians in identifying wound biofilm. Microscopy visualisation, when combined with molecular approaches, confirms biofilms are ubiquitous in DFUs and form either mono‐ or multi‐species biofilms. Clinical cues to aid clinicians in detecting wound biofilm are not accurate for use in DFUs. A paradigm shift of managing DFUs needs to consider anti‐biofilm strategies.